ASPECTS OF LEGAL PROTECTION FOR CHILDREN FROM CYBERCRIME - Ida Musofiana; Aji Sudarmaji; Ira Alia Maerani (Jurnal Pembaharuan Hukum, 2020)
The 21st century has progressed further. As in Indonesia, currently, the development of technology is increasingly rapid. This certainly affects aspects of social life in society and its security. Today's threats are not only enemies in the military, but also non-military. Among them are the threats faced by internet users, the penetration rate shows a high cumulation, opening up opportunities for the emergence of cyber-based crimes. The development of infrastructure is in line with the development of technology. Increasingly sophisticated technology is not only used by the community for positive things. However, not a few are taking advantage of technological sophistication to reap benefits that result in losses for technology users themselves. This study aims to research, examine how legal protection for children from cybercrime. In this case, children become vulnerable to cybercrime in digital era. Why is that? Considering that the control for internet access, as well as legal products in Indonesia, cannot yet fully guarantee protection for victims of cybercrime. The method used in this research is to use the descriptive analysis approach. Assessing and analyzing legal protection for children from cybercrime based on legal theories and applicable laws and regulations. Besides, it also reveals the phenomena of the current situation in the community.